AN IN-DEPTH ANALYSIS OF SELF-CARE STRATEGIES AND THEIR IMPACT AMONG DIABETES PATIENTS IN A DIABETIC CLINIC: A STUDY FROM MIRPURKHAS, PAKISTAN (The Research of Medical Science Review, 2024)
Diabetes is a chronic and progressive disease affecting lots of the population of the world, imposing significant burdens on healthcare systems, with proper self-care being pivotal to its effective management. This study assessed self-care activities, including diet, physical activity, foot care, medication adherence, and blood glucose monitoring among diabetic patients in Mirpurkhas, Pakistan, and evaluated their impact on patient outcomes. The cross-sectional study under consideration was conducted over a period of 3 months i.e. June 2024 to August 2024 with a sample size of 600 patients. It applied to the clinical setting and utilized a validated self-care questionnaire. Statistical analyses in SPSS have included frequencies, correlations, and regression tests to consider levels and effects of adherence across these domains. High adherence was recorded for medication as 90%, whereas foot care, physical activity, and dietary changes showed relatively lower adherence and were essential for controlling blood glucose and preventing complications. Findings suggest a need for education in self-care and targeted interventions in resource-limited settings. Recommendations for healthcare providers on health promotion in ways that enhance improved diabetic self-care practices are also presented here.